Effects of liquid metal particles on performance of triboelectric nanogenerator with electrospun polyacrylonitrile fiber films. (July 2019) - Ye, Qikai; Wu, Yongzhi; Qi, Yuanyuan; Shi, Lin; Huang, Shuyi; Zhang, Liang; Li, Menglu; Li, Wei; Zeng, Xiangyu; Wo, Hualei; Wang, Xiaozhi; Dong, Shurong; et al.
Abstract: Liquid metal (LM) has been used as flexible electrodes for high performance triboelectric nanogenerators (TENGs), however it is unclear how the LM in tribo-layers would affect the performance of TENGs. Here, we report the investigation on the effects of LM particles incorporated into a tribo-layer on the performance of TENGs. The TENGs consist of a polyacrylonitrile (PAN) electrospinning nanofiber membrane, and a polytetrafluoroethylene (PTFE) thin film. LM particles with different concentrations are incorporated into PAN polymer matrix, and used to make the PAN nanofibers membranes by electrospinning. Result shows that the outputs of TENGs become much larger with the increase in LM content. Specifically, the current density increases by about 40%, and both the charge density and output voltage increase by nearly 70%. The overall output power is approximately 2 times higher for the TENG with 1.5 wt% LM concentration, as compared to those of TENGs with pure PAN tribo-layer. However, the output of PAN/LM-PTFE TENGs deteriorates drastically when the LM mass content is increased to 2.5 wt%, at which the composite contains a high density of LM spheroid and spindle particles, deteriorating the generation of triboelectric charge. Graphical abstract: Liquid metal (LM) is feasible to be incorporated into electrospinning polymer (polyacrylonitrile, PAN) nanofibers as nano-particle and achieves the modification of TENG tribo-material layer on this account. Compared with TENG based on pure-PAN film, the TENG with PAN/LM composite membrane demonstrates a higher energy output, which only needs a small amount of LM concentration. The result exhibits that the current density increases by about 40% and the output voltage increase by nearly 70%, which is explained by the charge trapping mechanism. When two tribo-material layers begin to separate, a large negative bias generated by electron transfer from the external circuit will cause some electrons to be injected into the LM oxide layers, and then stored in the interface states. The low-cost approach in this study is also potential to other polymers, thus enriching the diversity of modifying tribo-material layers. In addition, it is also feasible to apply similar polymer composite membranes to the energy harvesting of wearable electronic devices. Image 1 Highlights: A simple process has been developed to incorporate liquid metal particles into PAN nanofibers uniformly. Liquid metal has been used as nanoparticle dopants to improve the TENG performance significantly The charge trapping at the liquid metal surface oxide plays the key role for the performance improvement of TENGs.